2016
DOI: 10.1186/s12889-016-3665-x
|View full text |Cite
|
Sign up to set email alerts
|

The connection between the primary care and the physical activity sector: professionals’ perceptions

Abstract: BackgroundTo stimulate physical activity (PA) and guide primary care patients towards local PA facilities, Care Sport Connectors (CSC), to whom a broker role has been ascribed, were introduced in 2012 in the Netherlands. The aim of this study is to assess perceptions of primary care, welfare, and sport professionals towards the CSC role and the connection between the primary care and the PA sector.MethodsNine focus groups were held with primary care, welfare and sport professionals within the CSC network. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
2
22
0
2
Order By: Relevance
“…All professions acknowledged having a task related to physical activity promotion, which is in line with previous studies [23][24][25][26][27][28]. However, in line with our previous interviews and focus groups [10,13], and results of other studies [23,24], general practitioners, nurse practitioners and dieticians mentioned several barriers to fulfilling these tasks (e.g., other priorities, time constraints, a lack of knowledge about sports and physical activities in the neighbourhood and a lack of knowledge about the prescription of physical activity). Care sport connectors and sports club and other physical activity facilities mentioned other barriers (e.g., a difficult target group and too few members to establish profitable groups).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All professions acknowledged having a task related to physical activity promotion, which is in line with previous studies [23][24][25][26][27][28]. However, in line with our previous interviews and focus groups [10,13], and results of other studies [23,24], general practitioners, nurse practitioners and dieticians mentioned several barriers to fulfilling these tasks (e.g., other priorities, time constraints, a lack of knowledge about sports and physical activities in the neighbourhood and a lack of knowledge about the prescription of physical activity). Care sport connectors and sports club and other physical activity facilities mentioned other barriers (e.g., a difficult target group and too few members to establish profitable groups).…”
Section: Discussionsupporting
confidence: 89%
“…Our previous studies [10,13] showed the perceptions of a limited number of care sport connectors and professionals from their experience within the network of a particular care sport connector. However, it is also relevant to reveal the overall perceptions of professionals towards the care sport connector function, their task execution and their willingness to collaborate intersectorally in a more general and comprehensive way.…”
mentioning
confidence: 99%
“…Furthermore, the existence of "Physical Activity Counseling Centers" in rehabilitation institutions with well-trained and skilled rehabilitation professionals address key factors on institutional (e.g., information during rehabilitation treatment, knowledge of professionals) and community level (e.g., collaborations). Although these inter-sectoral collaborations might be one of the successful elements of promoting physical activity in people with disabilities, it can be a challenge to establish and maintain these collaborations due to lack of time and/or differences in cultures and interests between sectors [57][58][59]. The counselors in the "Physical Activity Counseling Centers" may play a promising role in overcoming these challenges and therefore creating and maintaining a sustainable network between rehabilitation and community-based physical activity [9,60].…”
Section: Diversity Of Received Counselingmentioning
confidence: 99%
“…Within any HPpatient conversation about improving physical activity, both patients and HPs felt that providing patients with tangible physical activity opportunities to look in to, in contrast to 'you should get more exercise', was a preferable and more effective approach. However, for the HPs accessing or having the knowledge of different local physical activity groups and opportunities was a major barrier to being able to achieve this, a barrier previously identified for health promotion in primary care (36).…”
Section: Discussionmentioning
confidence: 99%
“…practice champion, community hub, or link worker) to be available for the local area in which they could signpost or formally refer patients towards. Similar to Leenaars et al (36), the link worker or community hub solution was seen by HPs to be able to bridge the connection between primary care and third party groups, providing the patients with more detailed information on the variety of options available in their local area. This type of resource was also seen to be a key solution to alleviate the time pressures HPs experienced within a consultation to discuss specific physical activity opportunities and supported the consensus that 20 patients can also self-refer to this type of resource and take responsibility for their own health improvement.…”
Section: Discussionmentioning
confidence: 99%